Effectiveness of Al-Qur'an Tadabbur Therapy on Nulliparous Women’s Anxiety Level during Labor - Nurul Auliya Kamila; Rosa Mutianingsih (Global Medical & Health Communication (GMHC), 2021)
The process of pregnancy affects psychological aspects significantly. This process may lead to anxiety and inconveniences. The previous research showed that anxiety might be contributing to the labor process. These can decreased baby birth weight and increased hypothalamic-pituitary-adrenal (HPA) hormone levels which cause changes in steroid hormone production and adult fertility rates. Besides, anxiety during pregnancy impacts emotional problems, disorders of hyperactivity, decentralization, and impaired child development. Nonpharmacological therapy that has been approved in reducing anxiety is religious copings. One of the religious copings is to contemplate (tadabbur) Al-Qur'an. Al-Qur'an can treat all kinds of diseases, including anxiety disorders. This study aims to examine the effect of Al-Qur'an tadabbur therapy on reducing nulliparous anxiety levels during labor. A quasi-experimental study was conducted with a pretest-postest control group design. The sampling technique was consecutive sampling. The number of 30 third trimester nulliparous women experienced moderate-severe anxiety levels in Tanjung Karang Public Health Center, Mataram was selected to participate in this study during July–September 2020. They were divided into two groups, the intervention and control groups. The intervention group received Al-Qur'an tadabbur therapy, while the control group was not. The statistical analysis used was univariate and bivariate analyses with an independent t test. The instrument was used as the Zung Self-Rating Anxiety Scale (SAS) questionnaire. This study showed that the decrease of anxiety score in the intervention group was 26.1% higher than the control group p=0.001 (p<0.05). In conclusion, Al-Qur'an tadabbur therapy is effective in reducing anxiety levels during labor. EFEKTIVITAS TERAPI TADABBUR AL-QUR’AN UNTUK MENURUNKAN TINGKAT KECEMASAN IBU PRIMIGRAVIDA DALAM MENGHADAPI PERSALINANProses kehamilan sering kali memengaruhi aspek psikologis yang dapat menyebabkan berbagai permasalahan seperti kecemasan dan ketidaknyamanan. Selain berdampak pada proses persalinan, kecemasan juga dapat mengakibatkan penurunan berat lahir dan peningkatan aktivitas hipotalamus-hipofisis-adrenal (HHA) yang menyebabkan perubahan produksi hormon steroid dan angka fertilitas saat dewasa. Selain itu, kecemasan pada masa kehamilan berkaitan dengan masalah emosional, gangguan hiperaktivitas, desentralisasi, dan gangguan perkembangan kognitif pada anak. Terapi nonfarmakologis yang telah disetujui dalam mengurangi kecemasan adalah religious coping. Salah satu religious coping adalah dengan tadabbur Al-Qur’an. Al-Qur’an merupakan pedoman yang mampu mengobati segala macam penyakit termasuk gangguan kecemasan. Penelitian ini bertujuan menguji efek terapi tadabbur Al-Qur’an terhadap penurunan kecemasan ibu hamil primigravida dalam menghadapi persalinan. Penelitian quasi-experiment dilakukan dengan pretest-postest with control group design, teknik pengambilan sampel dengan consecutive sampling. Subjek penelitian adalah 30 ibu hamil primigravida trimester III yang mengalami kecemasan sedang–berat di wilayah kerja Puskesmas Tanjung Karang, Kota Mataram pada bulan Juli–September 2020 yang terbagi dalam 2 kelompok, yaitu kelompok intervensi yang mendapat terapi Al-Qur’an dan kelompok kontrol. Analisis data menggunakan uji t independen. Penilaian tingkat kecemasan dilakukan menggunakan kuisioner Zung Self-Rating Anxiety Scale (ZSAS). Berdasar atas hasil penelitian, penurunan tingkat kecemasan kelompok intervensi 26,1% lebih tinggi dibanding dengan kelompok kontrol dengan taraf signifikasi p=0,001 (p<0,05). Simpulan, terapi tadabbur Al-Qur’an cukup efektif untuk menurunkan kecemasan pada ibu hamil dalam menghadapi persalinan.